A competitive advantage from the implementation timing of ISO management standards - Su, Hung‐Chung; Dhanorkar, Suvrat; Linderman, Kevin (Journal of Operations Management, 2015)
AbstractWith the rise of globalization, firms increasingly implement management standards developed by the International Organization for Standardization (ISO) to assure they can meet their customers’ expectations. ISO management standards reduce performance variability among suppliers and promote global trade. However, ISO standards also promote a certain degree of commonality or isomorphism between firms. If the very notion of ‘standards’ encourages a certain level of commonality between firms, then how can firms achieve a competitive advantage from implementing ISO standards? This research argues that thetimingof when a firm implements an ISO standard relative to their rivals has strategic benefits. Drawing on the competitive dynamics literature we argue that firms can achieve an early mover advantage when implementing ISO 14001. However, an early mover advantage depends on the level of a firm's absorptive capacity (prior experience with ISO 9001) and the competitive intensity of their industry. This study uses longitudinal data from firms that implemented ISO 14001 at varying points in time to examine the benefits of an early mover advantage. More broadly, this research sheds light onwhenfirms benefit the most from implementing new management standards. The results provide insights into implementing other emerging management standards.